ANALYSIS OF THE EFFECT OF FINANCIAL LITERATION, FINANCIAL TECHNOLOGY, INCOME, AND LOCUS OF CONTROL ON LECTURER FINANCIAL BEHAVIOR - Wahyudi Wahyudi; Brigitta Azalea Pulo Tukan; Dahlia Pinem (AFEBI Management and Business Review, 2020)
This research is a quantitative study that aims to determine the effect of financial literacy, financial technology, income, and locus of control on financial behavior. The population in this study were Lecturers at the Universitas Pembangunan Nasional Veteran Jakarta. The sample size was taken as many as 80 respondents, with methods through nonprobability sampling, purposive sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS 3.0 software. The results of this study indicate that (1) financial literacy has a significant positive effect on financial behavior. (2) financial technology has no influence and is not significant in financial behavior. (3) income has a significant positive effect on financial behavior. (4) locus of control does not influence financial behavior.